POSTGASTRORESECTION SYNDROMES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In the development of dumping syndrome, psychoneurological changes and disorders of the autonomic nervous system play a significant role. Clinically, dumping syndrome manifests itself with weakness, hot flashes, cold sweats, dizziness, palpitations, tachycardia, chest pain and tightness, and even fainting. The clinical manifestations of the disease and the severity of symptoms depend on the severity of dumping syndrome and the intake of food, especially sweet and dairy foods. Diagnosis of the process is anamnestic, clinically uncomplicated. X-ray examination shows accelerated contrast evacuation.